1985
DOI: 10.1016/0014-5793(85)81337-5
|View full text |Cite
|
Sign up to set email alerts
|

Methylammonium (ammonium) uptake in a glutamine auxotroph of the cyanobacterium Anabaena cycadeae

Abstract: Methylammonium uptake was studied in a glutamine auxotroph of the cyanobacterium Anabaena cycadeae lacking glutamine synthetase activity. The uptake pattern was found to be biphasic, consisting of an initial fast phase lasting up to 60 s followed by a slower second phase. When cells were preincubated with L-methionine-DL-sulphoximine, an irreversible inhibitor of glutamine synthetase activity, the second uptake phase was abolished although the first phase was unaffected. Since the glutamine auxotroph did not h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
1

Year Published

1986
1986
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 18 publications
1
15
1
Order By: Relevance
“…Further evidence that ANR activity in soil is regulated by glutamine formed by microbial assimilation of NH' was provided by studies showing that aminotransferase inhibitors that block metabolism of glutamine inhibited ANR activity in soil treated with NO-but did not do so in the presence of MSX (Table 3). Methylammonium (CH3NH+) labeled with 14C has been used as an NH'+ analog to study the carriers involved in transport of NH' across cytoplasmic membranes, and experiments using this compound have shown that MSX inhibits transport of CH3NH' across these membranes (17)(18)(19)(20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…Further evidence that ANR activity in soil is regulated by glutamine formed by microbial assimilation of NH' was provided by studies showing that aminotransferase inhibitors that block metabolism of glutamine inhibited ANR activity in soil treated with NO-but did not do so in the presence of MSX (Table 3). Methylammonium (CH3NH+) labeled with 14C has been used as an NH'+ analog to study the carriers involved in transport of NH' across cytoplasmic membranes, and experiments using this compound have shown that MSX inhibits transport of CH3NH' across these membranes (17)(18)(19)(20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…is able to use these amino acids as sole N-source for their growth and GS activity is essential for them to do so 19 . Using 14 C-methylammonium as probe, an energy-dependent and NO 3 --and NH 4 + -repressible ammonium transport system, that is essential for cyclic retention of ammonia in the cells, has been characterized in several cyanobacteria 16,17,29,30 . Typically, in all cases, 14 C-methylammonium uptake shows a biphasic curve, a rapid fi rst phase of accumulation lasting 60 s followed by a slower second phase linked to 14 C-methylammonium assimilation.…”
Section: Resultsmentioning
confidence: 99%
“…Addition of MSX 5 min after the addition of [ 14C]methylammonium caused an effect similar to that of ammonium addition, leading to an immediate efflux of 14C-label from the cells and cessation of any further uptake. The efflux caused by MSX has not been noted in other cyanobacteria (Rai et al, 1984;Singh et al, 1985;Rai & Prakasham, 1989) and may reflect the fact that unlike other cyanobacteria, Nostoc sp. ANTH metabolizes methylammonium as a nitrogen source.…”
Section: Eflect Of Msx On [ 14c]rnethylarnrnoniurn Uptake By N2-mentioning
confidence: 98%